Estudio de pre-factibilidad para la instalación de una planta productora de cerveza artesanal en Lima - Alvarez Burga, Daniel Martin (2017)
The study evaluates the commercial, technical, financial, economic and social viability of the installation of an ale craft beer microbrewery in Lima, composed of water, malted barley, hops and yeast. This craft beer is distinguished by its unique taste and exclusivity.